Of Earthquakes and Accumulations: Rewriting Indigeneity, Colonial Terror, and Modern Development in Kleist’s Das Erdbeben in Chili - Weihe, Will (Monatshefte für deutschsprachige Literatur und Kultur, 2024)
This article offers a settler colonial analysis of Kleist’s Erdbeben as the text itself critically unearths the antagonistic structures of modern colonial development. Kleist’s novella reworks the contemporary colonial literary technique of inscribing Indigeneity into nature, as Das Erdbeben re-envisions a native-natural rebellion that destabilizes the colonial narrative itself. In doing so, the text makes apparent the structures of colonial society that include the genocidal control of native lands and terrors of gendered violence. The novella presents typically unseen forms of native elimination through the highly visible violence against women that serves as a social basis for the European settler colony. I argue that, through the violent rupture of the earthquake, Kleist’s novella reimagines the perpetual threat of mass resistance among the oppressed and colonized groups, as well as the European counterrevolutionary formations that, in response to such rebellious threats, murderously shape the modern colonial world. (WW)